The African Inversion of Global Christianity: Religious Studies and Philosophical-Historical Aspects - Omelchenko, Yurii; Vitov, Andrii (Skhid, 2026)
This study is interdisciplinary in nature, integrating religious studies, political philosophy, and African studies. Drawing on Louis Hartz’s concepts of the "transplanted ideology" and the "freezing of ideological fragments," the article analyses the African "fragment" of Christianity that emerged free from European feudal traditions, the church-state conflict, and the secular critique of the Enlightenment. These conditions gave rise to an epistemologically autonomous religious system representing a distinct type of Christian modernity. Unlike European Christianity, which underwent a millennium of institutionalisation, the Reformation, and secularisation, African Christianity developed in conditions where these processes either did not occur at all or unfolded in a radically different sequence and configuration, producing the conditions for inversion — a new and syncretic variety of Christianity. Similar processes have taken place in other regions of the world, giving rise to Asian-syncretic, sub-Saharan, and Latin American variants of global Christianity. While Christianity is experiencing a crisis in Europe that is reflected in political processes, interest in the religion is, on the contrary, growing beyond the European continent, albeit in its autonomous and polycentric form. This shift marks a displacement of the centre of Christianity from Europe to the Global South, where approximately 70% of all Christians now reside. The most rapid growth in the number of Christians across all denominations is occurring in Africa. These findings were presented at the General Assembly of the World Evangelical Alliance (WEA), held in Seoul in October 2025. The study establishes that among the key reasons for the rapid growth of Christianity in Africa are its decentralisation, polycentrism, its separation from the historical memory shaped within the framework of European collective memory, and its paradoxical combination of tradition and modernity.